Pengaruh Pupuk Hayati dan Batuan Fosfat Alam terhadap Ketersediaan Fosfor dan Pertumbuhan Stroberi pada Tanah Andisol - Joko Maryanto; , Ismangil (Jurnal Hortikultura Indonesia, 2010)
ABSTRACTBiofertilizer has an important role in P-solubilization from phosphate rock, therefore it can be absorbed by plant. The organic acdid produced by biofertilizer can solve the phosphate mineral from phosphate rock. The objectives of the research were: to know the effect of biofertilizer and phosphate rock on the availability of P and the growth of strawberry at Andisol. The treatments included 2 levels of biofertilizer, i.e. 0 and 200 L . ha-1 and 5 levels of phosphate rock, i.e. 0; 100; 200; 400; and 800 kg P2O5 ha-1. The experiment was arranged in completely randomized block design with 3 replicates. The result showed that the application of biofertilizer and phosphate rock could increase the availability of P and total P of Andisols, dry weight of plant, lenght of plant and fresh weight of fruit .. Interaction between biofertilizer and phosphate rock could increase the soil pH.Key words: biofertilizer, phosphate rock, andisols, strawberry